Health and Safety in Contemporary Britain - Almond, Paul. author. aut Link
XIX, 317 p. 1 illus.
Keywords: This book analyses the perceived legitimacy of health and safety in post-1960 British public life. Since 2010 health and safety has appeared to be in crisis, being attacked by press, politicians and public alike, but are these claims of crisis accurate? How have understandings of health and safety changed over the past 60 years? By exploring the history, culture, and operation of health and safety in contemporary Britain, this book provides a new assessment of an understudied, but surprisingly far-reaching, part of the British political and social landscape. Combining archival research with focus group, social survey and oral history testimony, the book examines the historical background to health and safety, how health and safety has been enacted in public and in the workplace, the impact of changing economic, occupational and social structures on the operation of health and safety, and the conflicts and interests that have shaped the area.